1997
DOI: 10.1177/074193259701800306
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Strategies Used by General Educators and Teachers of Students with Learning Disabilities

Abstract: A survey was conducted to determine the instructional strategies used by special education teachers and general educators in teaching reading and writing, their philosophical approach (direct instruction or whole language), and what influenced teachers in making their philosophical decision. a 21-item questionnaire was completed by 183 elementary teachers of second and fifth grades and teachers of students with learning disabilities. the results indicated that the most important factor influencing respondents'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…Although the extent to which IEP goals and objectives translate to actual practice is not well known, the IEPs contained in this study may reflect common educational practice, and, by extension, special education practice. The study reviewed earlier by Drecktrah and Chiang (1997) is indicative of this trend.…”
Section: Why the Failure To Identify The Need For Basic Skills Instrumentioning
confidence: 82%
See 1 more Smart Citation
“…Although the extent to which IEP goals and objectives translate to actual practice is not well known, the IEPs contained in this study may reflect common educational practice, and, by extension, special education practice. The study reviewed earlier by Drecktrah and Chiang (1997) is indicative of this trend.…”
Section: Why the Failure To Identify The Need For Basic Skills Instrumentioning
confidence: 82%
“…For example, Drecktrah and Chiang (1997) sampled 300 elementary school teachers in Wisconsin and found that phonics instruction was used considerably more by second grade teachers than by fifth grade teachers, whether taught in separate lessons or embedded in context. In that study, elementary school teachers of learning disabled students in different grades reported higher rates of explicit phonics techniques compared to the regular classroom teachers in the fifth grade, but not in the second grade.…”
Section: Instructional Goals In Reading At the Different Grade Levelsmentioning
confidence: 98%
“…Öncelikli amaç, okuma ve yazmanın anlamını öğretme, okuduğunu anlama ve sözcükler arasında anlamsal ilişkiler kurma iken, fonik analiz bu beceriler kazandırıldıktan sonra öğretilir. Fonik analiz becerileri öğretilirken de rastgele ve az yapılandırılmış bir öğretim yapılır (Drecktrah, Chiang, 1997;O'Shea, O'Shea, Algozzine, 1998). Beraber kitap okuma, sessiz okuma, koro halinde okuma ve sesli okumalar yaklaşımın eğitim uygulamalarındandır (Katims, 1996;Mandlebaum, 1988;O'Shea ve diğerleri, 1998).…”
Section: Sosyal Etkileşimci Yaklaşımunclassified
“…Even though research has demonstrated the effectiveness of literature circles for general education classrooms, teachers of students with learning disabilities have not embraced this strategy with the same enthusiasm as their colleagues have. In fact, when Drecktrah and Chiang (1997) surveyed general educators and special education teachers in reference to instructional strategies used for teaching reading and writing, they found that only 24% of elementary-grade teachers who work with students with learning disabilities had used this strategy, compared with 44% of the second-grade teachers and 48% of fifth-grade teachers in general education. However, teachers of students with disabilities who have implemented this strategy have found promising results (Blum, Lipsett, & Yocum, 2002).…”
mentioning
confidence: 99%